2016
DOI: 10.1002/nau.23156
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year outcomes for the Altis® adjustable single incision sling system for treatment of stress urinary incontinence

Abstract: The Altis single-incision sling is a durable and effective treatment with a favorable safety profile for surgical treatment of women with stress or stress-predominant mixed urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 11 publications
6
26
2
Order By: Relevance
“…These are also the cases with higher failure rates. We do not think that hypermobility or ISD should be managed as dichotomous problems but rather as a continuous condition because frequently these two entities coexist . In fact, 91% of our present patients had urethral hypermobility in the physical examination with a positive Marshall–Bonney test.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These are also the cases with higher failure rates. We do not think that hypermobility or ISD should be managed as dichotomous problems but rather as a continuous condition because frequently these two entities coexist . In fact, 91% of our present patients had urethral hypermobility in the physical examination with a positive Marshall–Bonney test.…”
Section: Discussionmentioning
confidence: 62%
“…Kocjancic et al described an objective cure rate, evaluated with the cough stress test, of 88%. In that study, 90% of patients reported to be ‘very much better’ or ‘much better’, which we could assume to be equivalent to 9 or 10 points on the SVS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the scientific publications are retrospective observational studies, 13,15 and prospective single-center 16,17 or multicenter. 18 Our work is a prospective observational single-center study with a 6-year follow-up. The literature reviewed reports follow-ups at 1year, 13,16,19,20 2years 17,18 and 3years.…”
Section: Discussionmentioning
confidence: 99%
“…The SIMS presented was an adjustable polypropylene mesh, fixated in the obturator membrane with anchors, and introduced with a helicopasser (Altis® Single Incision Sling System; Coloplast®; The Netherlands). Single‐arm cohort studies show subjective and objective cure rates of 84% and 90%, respectively at 12‐month follow‐up, with durable results at 24‐month follow‐up …”
Section: Methodsmentioning
confidence: 99%
“…Single-arm cohort studies show subjective and objective cure rates of 84% and 90%, respectively at 12-month follow-up, with durable results at 24-month follow-up. 14,15…”
Section: Trade-off Experimentsmentioning
confidence: 99%